UNVEILING THE IMPACT OF LEADERSHIP AND MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. MULTI ALFA MANDIRI - Febriana Hamdani, Dhea; Triana Putri, Dian; Salsabila Nadhifa, Isad; Nurhalimah, Siti; Abdullah, Muhammad (Universitas Putera Batam, 2024)
This study aims to uncover the impact of leadership and motivation on employee performance at PT. Multi Alfa Mandiri. The primary issue addressed is the need to improve employee performance at the company, as well as the lack of previous scientific research on this topic at PT. Multi Alfa Mandiri. The research method employed is quantitative causal, with leadership and motivation as the independent variables and employee performance as the dependent variable. The population of this study consists of 150 employees, with a sample of 110 individuals selected using probability sampling with the simple random sampling technique. The results of the study indicate that leadership and motivation have both partial and simultaneous effects on employee performance at PT. Multi Alfa Mandiri. Based on these findings, recommendations are provided to the management of PT. Multi Alfa Mandiri to offer additional leadership training, implement open and honest communication with supervisors regarding team feelings when mistakes occur, enhance motivational aspects related to salary satisfaction by adjusting salaries to industry standards and employee performance capabilities, and provide regular training on the effective use of technology to increase work efficiency and prevent the misuse of technology for non-work-related purposes.